Studies on the Mechanism of Interaction of Congo Red with Lysozyme by Spectroscopic Methods - Li, X.H.; Lu, X.H.; Liang, J.P.; Xin, Z.J.; Zhou, X. (Asian Journal of Chemistry, 2013)
Interaction between Congo red and lysozyme was investigated by spectroscopic methods. The analysis of fluorescence data indicated the presence of both dynamic and static quenching mechanism in the binding of Congo red with lysozyme. Various binding parameters have been evaluated. The circular dichroism measurements revealed the conformational changes of lysozyme from a-helix to distorted helix structure thereby indicating the conformational change in lysozyme upon binding. The thermodynamic data showed that hydrophobic interactions playing a major role in Congo red binding to lysozyme.